(untitled) (Nordic Journal of African Studies, 2005)
The paper discovers and describes generalised usage patterns meant for assisting second language Swahili learners in appropriate use of the amba- locatives by applying corpus-based discovery procedures where the actual communication environment of each amba- locative relative is surveyed and the results used as a basis for determining the usage patterns. The patterns resulting from the analysis are obtained from an untagged corpus made from a selection of texts of contemporary Swahili literature. Patterns are not intended to be prescriptive rules but rather corpus-based generalisations which should guide learners of Swahili as a second language in producing acceptable sentences involving the use of ambapo, ambako, ambamo.